Organize - Beyes, Timon; Conrad, Lisa; Martin, Reinhold; Lovink, Geert; Rossiter, Ned (In Search of Media, 2019)
Digital media technologies re-pose the question of organization-and thus of power and domination, control and surveillance, disruption and emancipation. This book interrogates organization as effect and condition of media. How can we understand the recursive relationship between media and organization? How can we think, explore, critique-and perhaps alter-the organizational bodies and scripts that shape contemporary life?